Pengaruh Pendekatan Student Center Learning terhadap Hasil Belajar Pendidikan Jasmani - Ekowati Ekowati; Nurul Husnul Lail; Habibie Habibie; Eskawida Eskawida; Singgih Prastawa; I Ketut Addy Putra Indrawan (Journal on Education, 2023)
Student center learning is a learning approach that focuses on students during the teaching and learning process to achieve maximum learning outcomes. In this context, learning outcomes are considered as a measure of the success of an educational program and can help teachers determine effective teaching strategies. This research aims to examine the effect of the student center learning model on physical education learning outcomes. The sample used in this study consisted of 16 students from the Elementary School Teacher Education Program at Triatma Mulya University who participated in the program during the odd semester of the 2022/2023 academic year. This study used an experimental method with data collection techniques through tests. The results of the study show that the student center learning model has a significant effect on physical education learning outcomes with a significance value of 0.000 < 0.05. Based on these findings, it is recommended to develop effective teaching strategies based on the research results to improve physical education learning outcomes through the implementation of the student center learning model.